How the Market Became Divine. Issue 1 (March 2016) - Cox, Harvey
Abstract: We have moved beyond a "market economy" to what some have called a "market society, " one in which everything seems to be for sale. We also now see the advent of a "market religion, " in which the values and life meanings of consumer culture have become dominant. This new religion has its own doctrines, rituals, priesthood, and mission to "go into all the world." It has its own narratives of creation, fall, and redemption, and its own saints and heroes. But because its underlying thrust is endless growth, and we live on a finite planet, it is carrying us toward destruction. Some parts of Christianity are opposing what Pope Francis has called "idolatry, " but unfortunately most parts are being swept into its new dispensation.